Oral Presentations Abstracts: LOOKING AT OVERTREATMENT IN ESTHETIC DENTISTRY AS A PROFESSIONAL AND BUSINESS APPROACH - MESTER, Alexandru; ALUAS, Maria; BORDEA, Roxana; LUCACIU, Ondine (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Dental practitioners, sometimes, are facing patient’s requests to overtreatment care, which in many situations is completely unnecessary or even dangerous/ risky/ disproportionate to the patient’s (oral) health state/condition. It can include procedures such as: teeth whitening, removal of amalgam fillings, closing diastema, veneers, dental extractions, root canal treatment, dental implants or fixed orthodontic appliances. It is known that dentistry practice belongs to two different and conflicting worlds, medical and business. In front of such situations, dentists should decide the right way of doing their job: being a medical doctor and treating patients or doing business and executing exactly what patients are asking for. Due to these facts, this presentation aims to: 1) identify the main issues related to this dilemma of dentists and 2) offer a better perspective on realizing dental esthetics treatments without jeopardize the oral health of the patient, but also the dentist’s profession and professional integrity.